The Religious Court's Decisions on Divorce: A Maqāṣid Sharīʿa Perspective - Muchamad Coirun Nizar (Universitas Islam Negeri Mataram, 2020)
Maqāṣid sharīʿa is considered as a theory that can be applied to analyze the objectives of Islamic law. One of the developments of Islamic law in Indonesia, and in the Muslim world in general, is concerned with religious courts’ decision made by judges. This study analyzes court decisions from the maqāṣid sharīʿa perspective. This qualitative study focused on the divorce cases from the religious court of Salatiga district, Central Java. Twenty percent of the cases in 2017 were proportionally selected. This study shows that there were various reasons of divorce, ranging from constant quarrels to spousal negligence. The other reason was conversion, where one couple left Islam. The court decisions on those divorce cases suggest that the judges attempt to uphold the principles of maqāṣid sharīʿa, such as the preservation of life, descendant, asset and religion. Depending on the respective case, the judges may grant the petition if it will give a greater benefit to the parties concerned that does not contrary to the maqāṣid sharīʿa.